2018
DOI: 10.1590/1982-0224-20170150
|View full text |Cite
|
Sign up to set email alerts
|

Fish diversity in the cascade of reservoirs along the Paranapanema River, southeast Brazil

Abstract: The Paranapanema River is a major tributary of the upper Paraná river basin. Eleven hydropower dams regulate its main course, but no study has investigated fish diversity in these impoundments at the basin-scale. The present study investigated spatial patterns of richness, composition, and abundance of native (non-migratory and migratory) and non-native fishes in the cascade of reservoirs along the Paranapanema River. The study is based on data collected from 34 independent studies conducted in nine reservoirs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 62 publications
4
32
2
3
Order By: Relevance
“…Species richness observed in this study is in accordance with some previous studies conducted in nearby areas, with an average of 40–50 species (Nobile et al, ; Pelicice, Azevedo‐Santos, Esguícero, Agostinho, & Arcifa, ; Queiroz et al, ). The diversity indices corroborated hypothesis 1 (Willis & Magnuson, ) because the transition area exhibited the greatest species richness, abundance and biomass with increase in the wet season.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Species richness observed in this study is in accordance with some previous studies conducted in nearby areas, with an average of 40–50 species (Nobile et al, ; Pelicice, Azevedo‐Santos, Esguícero, Agostinho, & Arcifa, ; Queiroz et al, ). The diversity indices corroborated hypothesis 1 (Willis & Magnuson, ) because the transition area exhibited the greatest species richness, abundance and biomass with increase in the wet season.…”
Section: Discussionsupporting
confidence: 92%
“…In dam-free rivers, flood pulses tend to homogenise the different habitats present in a flood plain, such as rapids, river corridors and marginal lagoons (Thomaz et al, 2007), by connecting all these environment. However, in this study an inverse situation was observed, with more similar habitats in the dry season, since, in the Species richness observed in this study is in accordance with some previous studies conducted in nearby areas, with an average of 40-50 species Pelicice, Azevedo-Santos, Esguícero, Agostinho, & Arcifa, 2018;Queiroz et al, 2015Queiroz et al, , 2016.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, a better understanding of the effects of reservoir cascades on fish assemblages is necessary, particularly in Brazil, where hydropower represents the country's main energy source. Studies of reservoir cascades in Brazilian rivers have demonstrated that fish composition, richness, and functional diversity change with a longitudinal gradient along the cascade and over time (Ferrareze, Nogueira, & Sartori, 2014;Oliveira, Baumgartner, Gomes, Dias, & Agostinho, 2018;Pelicice, Azevedo-Santos, Esguícero, Agostinho, & Arcifa, 2018;Pereira et al, 2018;Petesse & Petrere, 2012;dos Santos et al, 2017), both in reservoirs (lentic environment) Bailly et al, 2016;Ortega et al, 2018), and also downstream from dams (lotic environment) (Granzotti, Miranda, Agostinho, & Gomes, 2018;de Mérona, Vigouroux, & Tejerina-Garro, 2005;Zdankus, Vaikasas, & Sabas, 2008). Impoundments change the river's flow regime by reducing variability in annual discharge and flood pulses, which in turn impact ecological processes in downstream habitat (Bunn & Arthington, 2002;Pompeu & Godinho, 2006).…”
mentioning
confidence: 99%
“…This abrupt and permanent intervention in the characteristics of physical habitats may affect the reproductive and recruitment patterns of most fish species (Agostinho et al, 2004). In particular, migratory fish, like P. hemioliopterus, may be prevented from completing their reproductive migrations due to the obstruction of the river, which impedes the fish from reaching suitable spawning locations (Antonio et al, 2007;Pelicice et al, 2018), which could eventually lead to local population decline and even extinction.…”
Section: Discussionmentioning
confidence: 99%